2023
DOI: 10.1038/s43247-022-00673-6
|View full text |Cite
|
Sign up to set email alerts
|

A topographic hinge-zone divides coastal and inland ice dynamic regimes in East Antarctica

Abstract: The impact of late Cenozoic climate on the East Antarctic Ice Sheet is uncertain. Poorly constrained patterns of relative ice thinning and thickening impair the reconstruction of past ice-sheet dynamics and global sea-level budgets. Here we quantify long-term ice cover of mountains protruding the ice-sheet surface in western Dronning Maud Land, using cosmogenic Chlorine-36, Aluminium-26, Beryllium-10, and Neon-21 from bedrock in an inverse modeling approach. We find that near-coastal sites experienced ice buri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(197 reference statements)
0
1
0
Order By: Relevance
“…By dating the rocks that have been exposed due to ice retreat, we can determine the timing of the ice retreat. The cosmogenic nuclide dating of erratic and bedrock collected at various altitudes has been utilized to reconstruct the changes in heights of the EAIS since the Last Glacial Maximum (Andersen et al, 2023;Balco et al, 2023;Kawamata et al, 2020;Suganuma et al, 2014;Johnson et al, 2020;Suganuma et al, 2022;White et al, 2011;White and Fink, 2014;Yamane et al, 2011). Recent studies in Dronning Maud Land revealed early to mid Holocene ice-sheet thinning, indicating a discrepancy (delay) in the timing of deglaciation in previous studies that employed the ICE-6G model (Argus et al, 2014;Peltier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By dating the rocks that have been exposed due to ice retreat, we can determine the timing of the ice retreat. The cosmogenic nuclide dating of erratic and bedrock collected at various altitudes has been utilized to reconstruct the changes in heights of the EAIS since the Last Glacial Maximum (Andersen et al, 2023;Balco et al, 2023;Kawamata et al, 2020;Suganuma et al, 2014;Johnson et al, 2020;Suganuma et al, 2022;White et al, 2011;White and Fink, 2014;Yamane et al, 2011). Recent studies in Dronning Maud Land revealed early to mid Holocene ice-sheet thinning, indicating a discrepancy (delay) in the timing of deglaciation in previous studies that employed the ICE-6G model (Argus et al, 2014;Peltier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%